Methods, directions and basic results to the lab work on female Atlantic cod (Gadus morhua) gonad samples - Falkensteiner, Stefan, 1980- (2014)
Final report to the course “LÍF038M Research project in biology for foreign students" The aim of the lab work is to examine female gonad samples, collected in the Eastfjords of Iceland in spring 2013, in respect of spawning time. Several oocyte parameters, e.g. mean diameter, roundness, etc. where measured and some basic analysis on the data was conducted. It is proposed that the variation in oocyte diameters will decrease as the spawning progresses, i.e. as relatively more hydrated oocytes are inside the gonads. Additionally the average oocyte diameter should increase with proceeding spawning time. This report firstly summarizes the method and gives directions to be used as a manual for a replication at a later date. Secondly it shows the results of the measurements and introduces a brief data analysis. The lab work was done within the university course “Research project in biology for foreign students” and is part of a comprehensive PhD project on Atlantic cod (Gadus morhua) reproduction conducted at the Marine Academic Research in Iceland (MARICE).